1985
DOI: 10.1056/nejm198504113121501
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tubal Infertility in Relation to the Use of an Intrauterine Device

Abstract: Women who use an intrauterine device (IUD) are at increased risk of acute pelvic inflammatory disease, but the relation of the IUD to subsequent infertility is not established. We interviewed 159 nulligravid women with tubal infertility to determine their prior use of an IUD. Their responses were compared with those of a matched group who conceived their first child at the time the infertile women started trying to become pregnant. The risk of primary tubal infertility in women who had ever used an IUD was 2.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(52 citation statements)
references
References 19 publications
2
48
1
1
Order By: Relevance
“…A forgotten IUCD can lead to a range of problem starting from infertility [2] to actinomycosis in post menopausal period [3] to Pelvic inflammatory disease [4] . Removal of embedded IUCD is quite difficult .Ultrasound can guide the location and help in removal [5] but hysteroscopy is the best [6] .…”
Section: Discussionmentioning
confidence: 99%
“…A forgotten IUCD can lead to a range of problem starting from infertility [2] to actinomycosis in post menopausal period [3] to Pelvic inflammatory disease [4] . Removal of embedded IUCD is quite difficult .Ultrasound can guide the location and help in removal [5] but hysteroscopy is the best [6] .…”
Section: Discussionmentioning
confidence: 99%
“…More detailed methods for case and control selection are presented elsewhere. 4 For the purpose of the present analysis, we chose the subgroup of women defined as being infertile (those who did not conceive despite trying for at least one year) in whom an ovulatory abnormality was present ( Table 1). The In addition to the matching variables, we also analyzed other variables that might be related to either exercise or infertility, including socioeconomic variables (level of income, education, and social class of the occupation of respondents and their spouses), past birth control use, number of past sexual partners, past drug and smoking habits, and history of sexually transmitted diseases.…”
Section: Methodsmentioning
confidence: 99%
“…In the mid and late 1970s, multiple studies confirmed the Dalkon Shield's strong association with pelvic inflammatory disease [44] [45], spontaneous abortion [46], ectopic pregnancy, and infertility [47] [48]. These studies led to recommendations that IUDs should be avoided in nulliparous women, teenagers, and populations at increased risk for PID [49].…”
Section: Dalkon Shield Fall-outmentioning
confidence: 99%